Establishment of Wind Gust Estimation Equation in Bohai Sea - Hu, Haichuan; Huang, Bin; Dai, Kan; Qu, Hongyu (Frontiers in Earth Science, 2022)
Wind gusts over the ocean can have a great influence on maritime transport and production operations. However, owing to the scarcity of marine observation data and the complex causes of wind gusts, the estimation and forecasting of gusts at sea are even more difficult. In this study, a gust estimation equation applicable to the Bohai Sea is established based on observation and reanalysis data, with representative observation stations on the coast and offshore in the Bohai Sea. During the process, partial correlation analysis and a significance test of correlation coefficient differences were used to further clarify the influence of average wind speed and vertical wind shear at different heights on wind gusts. The final gust estimation equation includes a mean wind speed term, a turbulence term, and a convection term, which are statistically significant contributors; in addition, there are clear physical meanings. Comparing two gust factor methods in this study, the average errors and fitting errors of the least squares gust estimation equation are the smallest. For wind gusts between 10 and 26 m/s, the fitting error in the gust estimation equation is 7.68–12.25% and 21.10–30.08% lower than those of the two gust factor methods in this study. The gust estimation equation better reflects the difference of wind gusts typical under different average wind speeds and vertical wind shear conditions, so a better prediction for wind gusts can be achieved.